Sunday

April 20, 2014

April 20, 2014

Posted by **Erica** on Monday, December 5, 2011 at 12:42pm.

x^2-23x+c

x^2-(2/7)x+c

- Algebra 2 -
**Reiny**, Monday, December 5, 2011 at 1:25pmtake half the middle term coefficient, square it

x^2 - 23x + 526/4

= (x- 23/2)^2

looks like you learning the process of "completing the square"

here is an easier one ...

x^2 + 10x + c

or

x^2 + 10x +**25**,,,,,(half of 10 is 5, 5^2 = 25)

= (x+5)^2

expand (x+5)^2 to see why this happens

Now try your own second question and let me know what you got for c .

**Related Questions**

Algebra 2 - Find a value(s) that makes the expression y^2 - 16 ---------- ...

Algebra - Use the intermediate theorem to show that the polynomial function ...

algebra - 2.) Use algebra to find the value of a in the triangle when x=a, y=2a...

Algebra - 5x=1/2y-1, find value of X; 1/4y=10x-1, find value of Y (use ...

Algebra - w=Cr^-2 Suppose that an object is 100 pounds when it is at sea level. ...

Trigonometry - The wheel makes 6 complete revolutions every 60 seconds. From ...

Algebra - Find the vertex of the functions given below. 1. y=(x-4)(x+2) 2. y=2x^...

Algebra 1 - I need help to this mathe problems... 1.Elimination using ...

Algebra - 6a=(5(3+b+a)-9, find value of a; 3(a-b)+4b=5(1+6), find value of b

algebra - Which value of x makes the following equation true? 7.8(x - 2) = -0.2x...